COVID-19, the Church, and the Challenge to Ecumenism - Plüss, Jean-Daniel (Transformation, 2020)
The COVID-19 pandemic raises questions how churches respond to an extraordinary situation where not only health and economic issues are at stake, but also the understanding of what church is all about and how ecclesial life is practised. Furthermore, do the current experiences have any bearing about the way churches of different traditions relate to each other? This article introduces the issues raised by first reviewing how Christians in past centuries have faced pandemics. Second, the text will look at current responses by large church bodies and organizations. Thirdly, a small survey will focus on the responses by local churches across the globe as to the benefits and challenges associated with the present coronavirus crisis. Finally, the paper addresses what the various reactions tell us about a reassessment of the nature of the church, both in the local context and with regard to the wider Body of Christ.